Impact of Mn/Co substitution on magnetoelectric and structural properties of ZnO nanostructures thin films - Ángela P. Lanchero; Lina F. Prieto; Heiddy P. Quiroz; Jorge A. Calderón; A. Dussan; F. Mesa (Heliyon)
This work investigates the impact of Mn and Co doping on the structural, morphological, electrical, and magnetic properties of ZnO thin films deposited via DC magnetron co-sputtering. Doping concentration, substrate temperature, and substrate type (soda-lime glass and oriented silicon wafer) were systematically varied for potential spintronic applications. X-ray diffraction (XRD) and Raman spectroscopy confirmed the formation of a hexagonal wurtzite crystalline structure with a preferential [002] growth orientation when Mn was incorporated into the ZnO matrix. Raman analysis also ruled out the presence of secondary Co oxide phases in ZnO:Co samples. Films doped with Mn at 25 W exhibited compressive stress of −0.345 %, which increased to −2.03 % at 50 W, highlighting the dopant's impact on lattice strain. FTIR spectra revealed characteristic bands of ZnO:Co, indicating successful incorporation of Co ions into the matrix. SEM and magnetic force microscopy (MFM) showed granular surface morphology and cluster formation at higher Mn concentrations (50 W). Electrical measurements revealed unipolar and bipolar resistive switching (RS) behaviors, associated with the Schottky barrier model, and strongly influenced by substrate temperature and doping levels. Notably, samples doped with Co at 50 W exhibited enhanced interfacial RS properties. Vibrating sample magnetometry (VSM) demonstrated room-temperature ferromagnetic hysteresis in films synthesized at Ts = 423 K, with Mn (25 W) and Co (50 W) doping. These findings validate the potential of ZnO:Mn/Co as a dilute magnetic semiconductor (DMS) for spintronic applications, offering tailored magnetic and resistive properties through precise control of doping and synthesis parameters.